Fragment-based discovery of potent ERK2 pyrrolopyrazine inhibitors. Issue 21 (1st November 2015) - Burdick, Daniel J.; Wang, Shumei; Heise, Christopher; Pan, Borlan; Drummond, Jake; Yin, JianPing; Goeser, Lauren; Magnuson, Steven; Blaney, Jeff; Moffat, John; Wang, Weiru; Chen, Huifen
Graphical abstract